Determinan Harga Saham dengan Nilai Perusahaan sebagai Variabel Intervening pada Perusahaan Sektor Konstruksi Bangunan - Dedi Dwi Arseto; Mangasi Sinurat (Jurnal Pasar Modal dan Bisnis, 2020)
The purpose of this study was to determine the effect of DER, EPS, and ROA on stock prices with company size as an intervening variable. The population of this research is companies in the building construction sector registered at BIE in 2014 to 2018. The samples used were 5 companies using perposive sampling techniques. The analysis method used is path analysis. Research Results The direct effect of Debt Equity Ratio on stock prices shows positive and significant results. While the indirect effect of positive Debt Equity Ratio is not significant on stock prices through firm value. The direct effect of Return On Assets on stock prices has not significant positive results. The indirect effect of Return On Assets on stock prices through the value of the company obtained insignificant positive results. The direct effect of Erning Per Share on stock prices obtained significant positive results. The indirect effect of Erning Per Share on stock prices through the value of the company obtained insignificant positive results. The value of the company on stock prices has a significant positive effect on companies in the construction sector in the period 2014 to 2018.